Tiburón - González, Andrés (My University, 2013)
El tema de este recurso es la locomoción animal del tiburón. Se trata de un interactivo para que el usuario pueda entender cómo se desplaza este animal.

The topic of this resource is the shark locomotion. It consists of an interactive infographic that helps the user understand how this animal moves.
Keywords: Infografías; Interactivo; Tiburón; Locomoción